Success of Social Sciences Learning in Fourth Grade Elementary School Students in Buay Madang Timur Sub-district: Is There a Connection Between Self-efficacy and Self-directed Learning? - Baharudin; Nur Asiyah; Ida Fiteriani; Abu Dharin (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2024)
This research aims to explore and understand the potential relationship between self-efficacy and students' self-directed learning at the Elementary School level. The research design employed is quantitative associative research with a correlational design. A total of 80 students from three elementary schools were selected as research subjects using cluster sampling without specific divisions. Unlike previous studies that tend to discuss self-efficacy and independent learning in general terms, this study offers a specific approach focusing on the subject of Social Studies (IPS). Social Studies was chosen due to its significant role in developing students' understanding of history, geography, and the social and cultural dynamics that shape their identity. The results of the analysis using T-tests and correlation tests indicate a significant correlation, providing evidence of a tangible relationship between the levels of self-efficacy and self-directed learning among students in the subject of Social Sciences (IPS). The implications of this research go beyond understanding this relationship, offering potential contributions to educational practices. The findings can serve as a reference for educators and educational practitioners to better understand how to enhance students' self-efficacy and self-directed learning. Furthermore, this research provides a foundation for taking further actions to address issues related to self-efficacy and self-directed learning in the elementary education environment. Therefore, it is hoped that this research will provide substantial benefits for educational development, especially in enhancing the effectiveness of student learning at the Elementary School level in the subject of Social Sciences (IPS).